2018
DOI: 10.1002/jsfa.9329
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the effect of blue light on microRNAs involved in the accumulation of functional metabolites of longan embryonic calli through RNA‐sequencing

Abstract: The results of the study revealed that the expressions of phase-specific miRNAs vary with the change of functional metabolites in longan ECs. This study provides new insights into the molecular mechanisms that allow light to influence plant metabolism. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 71 publications
2
12
0
Order By: Relevance
“…DEGs that regulate starch and sucrose were found in the DB and DW comparisons (Figure 5A,B) and the expression levels of most genes in the blue light treatment group were higher than those in the other groups (Figure 5C). These results further confirm the contribution of blue light to biotin and polysaccharide synthesis in longan ECs, which is consistent with the results of Li et al [23].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…DEGs that regulate starch and sucrose were found in the DB and DW comparisons (Figure 5A,B) and the expression levels of most genes in the blue light treatment group were higher than those in the other groups (Figure 5C). These results further confirm the contribution of blue light to biotin and polysaccharide synthesis in longan ECs, which is consistent with the results of Li et al [23].…”
Section: Resultssupporting
confidence: 93%
“…In addition, heat map analysis of DEGs demonstrated that the expression levels of most genes in secondary metabolic pathways were significantly higher under blue light treatment than under the other treatments (Figure 6C). The above results indicate that blue light is most beneficial for promoting the accumulation of carotenoids, alkaloids and total flavonoids in longan ECs, which is consistent with the results of Li et al [23].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Freeze-dried grains of D. officinale stems and leaves were extracted as previously described (Li et al, 2018). The absorbance was measured with a UV-visible spectrophotometer (Evolution 350, Thermo Fisher, MA, USA), and the wavelengths of polysaccharides, flavonoids and alkaloids were measured at 485 nm, 510 nm and 416 nm, respectively (Li et al, 2018). The polysaccharide, flavonoid and alkaloid contents in the D. officinale stems and leaves were calculated according to established standard curves.…”
Section: Secondary Metabolite Determinationmentioning
confidence: 99%